Fluralaner systemic treatment of chickens results in mortality in Triatoma gerstaeckeri, vector of the agent of Chagas disease - Cassandra Durden; Yuexun Tian; Koyle Knape; Cory Klemashevich; Keri N. Norman; John B. Carey; Sarah A. Hamer; Gabriel L. Hamer (Parasites & Vectors)
Abstract Background Chagas disease remains a persistent vector-borne neglected tropical disease throughout the Americas and threatens both human and animal health. Diverse control methods have been used to target triatomine vector populations, with household insecticides being the most common. As an alternative to environmental sprays, host-targeted systemic insecticides (or endectocides) allow for application of chemicals to vertebrate hosts, resulting in toxic blood meals for arthropods (xenointoxication). In this study, we evaluated three systemic insecticide products for their ability to kill triatomines. Methods Chickens were fed the insecticides orally, following which triatomines were allowed to feed on the treated chickens. The insecticide products tested included: Safe-Guard® Aquasol (fenbendazole), Ivomec® Pour-On (ivermectin) and Bravecto® (fluralaner). Triatoma gerstaeckeri nymphs were allowed to feed on insecticide-live birds at 0, 3, 7, 14, 28 and 56 days post-treatment. The survival and feeding status of the T. gerstaeckeri insects were recorded and analyzed using Kaplan–Meier curves and logistic regression. Results Feeding on fluralaner-treated chickens resulted 50–100% mortality in T. gerstaeckeri over the first 14 days post-treatment but not later; in contrast, all insects that fed on fenbendazole- and ivermectin-treated chickens survived. Liquid chromatography tandem mass spectrometry (LC-QQQ) analysis, used to detect the concentration of fluralaner and fenbendazole in chicken plasma, revealed the presence of fluralaner in plasma at 3, 7, and 14 days post-treatment but not later, with the highest concentrations found at 3 and 7 days post-treatment. However, fenbendazole concentration was below the limit of detection at all time points. Conclusions Xenointoxication using fluralaner in poultry is a potential new tool for integrated vector control to reduce risk of Chagas disease. Graphical Abstract